Potensi Conotoxin dari Conus Spesies sebagai Analgesik - Izzatiana Nabila Ramadhani; Nani Wijayanti Dyah Nurrahman; Giftania Wardani Sudjarwo (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2022)
Pain is an unpleasant sensory and emotional experience resulting from actual or potential tissue damage or tends to damage tissue. Analgesic is one of the therapies commonly used to relieve pain. Analgesic itself is divided into two types, namely opioids and non-opioid, where each of these drugs has effectiveness and side effects. Researchers are trying to find other alternatives that have the potential as analgesics, with high effectiveness and fewer side effects. Conotoxin is a venom derived from Conus and it has potential as an analgesic. One form of Conotoxin that has been developed is Ziconotide. Ziconotide works by activating miu receptors that block N-type calcium channels through the G protein mechanism so that the transmission of pain signals to nerve cells can be inhibited at the spinal cord level. This review article aims to evaluate the use of Ziconotide as an analgesic. The evaluation was carried out by considering the effectiveness and the emergence of side effects from 10 article related to Ziconotide based on inclusion and exclusion criteria. The results obtained from this review article are that Ziconotide has a fairly high effectiveness as an analgesic, this can be proven by the number of patients experiencing pain reduction of more than 30% at least 40% of the population in each literature, as well as side effects that can be said to be quite mild.